Ovarian absence: a systematic literature review and case series report - H. Alexander Chen; Alyssa A. Grimshaw; Melissa Taylor-Giorlando; Pavithra Vijayakumar; Dan Li; Miranda Margetts; Emanuele Pelosi; Alla Vash-Margita (Journal of Ovarian Research, 2023)
Abstract Ovarian absence is an uncommon condition that most frequently presents unilaterally. Several etiologies for the condition have been proposed, including torsion, vascular accident, and embryological defect. A systematic review was conducted to describe the clinical presentation of ovarian absence, as well as its associations with other congenital anomalies, through a systematic search of Cochrane Library, ClinicalTrials.gov, Google Scholar, Ovid Embase, Ovid Medline, PubMed, Scopus, and Web of Science. Exclusion criteria included cases with suspicion for Differences of Sex Development, lack of surgically-confirmed ovarian absence, and karyotypes other than 46XX. Our search yielded 12,120 citations, of which 79 studies were included. 10 additional studies were found by citation chasing resulting in a total 113 cases including two unpublished cases presented in this review. Abdominal/pelvic pain (30%) and infertility/subfertility (19%) were the most frequent presentations. Ovarian abnormalities were not noted in 28% of cases with pre-operative ovarian imaging results. Approximately 17% of cases had concomitant uterine abnormalities, while 22% had renal abnormalities. Renal abnormalities were more likely in patients with uterine abnormalities (p < 0.005). Torsion or vascular etiology was the most frequently suspected etiology of ovarian absence (52%), followed by indeterminate (27%) and embryologic etiology (21%). Most cases of ovarian absence are likely attributable to torsion or vascular accidents, despite many references to the condition as “agenesis” in the literature. Imaging may fail to correctly diagnose ovarian absence, and diagnostic laparoscopy may be preferable in many cases as genitourinary anatomy and fertility considerations can be assessed during the procedure. Fertility is likely minimally or not affected in women with unilateral ovarian absence.